2017
DOI: 10.1016/s1474-4422(17)30328-9
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale identification of clinical and genetic predictors of motor progression in patients with newly diagnosed Parkinson's disease: a longitudinal cohort study and validation

Abstract: BackgroundBetter understanding and prediction of PD progression could improve disease management and clinical trial design. We aimed to use longitudinal clinical, molecular, and genetic data to develop predictive models, compare potential biomarkers, and identify novel predictors for motor progression in PD. We also sought to assess the use of these models in the design of treatment trials in PD.MethodsA Bayesian multivariate predictive inference platform was applied to data from the Parkinson’s Progression Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
137
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(142 citation statements)
references
References 42 publications
(39 reference statements)
5
137
0
Order By: Relevance
“…Furthermore, the accumulation of genetic risk factors can have a significant impact on diagnostic and prognostic strategies, as shown for other complex diseases such as Parkinson's disease 71 . Furthermore, the accumulation of genetic risk factors can have a significant impact on diagnostic and prognostic strategies, as shown for other complex diseases such as Parkinson's disease 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the accumulation of genetic risk factors can have a significant impact on diagnostic and prognostic strategies, as shown for other complex diseases such as Parkinson's disease 71 . Furthermore, the accumulation of genetic risk factors can have a significant impact on diagnostic and prognostic strategies, as shown for other complex diseases such as Parkinson's disease 71 .…”
Section: Discussionmentioning
confidence: 99%
“…1 As the basis of their work, the investigators used data from two observational clinical studies in patients with Parkinson’s disease and healthy controls, including data from genetics, imaging, biologics, and clinical assessments: the Parkinson Progression Markers Initiative (PPMI), 2,3 and the Longitudinal and Biomarker Study in Parkinson Disease (LABS-PD). 4 Latourelle and colleagues aimed to construct a clinically useful predictive model of Parkinson’s disease motor progression based on previously established and potential novel markers.…”
mentioning
confidence: 99%
“…Using machine-learning approaches on various clinical, imaging, CSF and genetic data, one recent study concluded that imaging data was unable to predict motor progression in de novo PD. 23 However, in this study, DAT SPECT was the only imaging biomarker. 23 We also found SPECT to be poor at predicting disease progression.…”
Section: Discussionmentioning
confidence: 73%
“…23 However, in this study, DAT SPECT was the only imaging biomarker. 23 We also found SPECT to be poor at predicting disease progression. On the contrary, another study using radiomics analysis on SPECT images at baseline and one…”
Section: Discussionmentioning
confidence: 73%